Toxicity Test of Shallot Skin Extract (Allium ascalonicum) on Mortality of Leaf Roller Caterpillar (Spoladea recurvalis) - Supriatno; Raiyatul Jannah Raiya; Safrida; Hafnati; Samingan (Postgraduate, University of Mataram, 2023)
Pests are creatures that destroy crops and, in general, hurt farmers financially. The leaf roller caterpillar is one of the pests that can result in crop loss in horticultural crops, particularly spinach. Vegetable pesticides, including shallot skin extract, can effectively and sustainably control the pest leaf roller caterpillars. This study sought to ascertain the impact of shallot skin extract on leaf roller caterpillar mortality after 48 hours of treatment. The experimental study design with a completely randomized design (CRD), 7 treatments, 4 replications, and a total of 28 treatments was employed. P0 (negative control), P1 (10,000 ppm), P2 (20,000 ppm), P3 (30,000 ppm), P4 (40,000 ppm), P5 (50,000 ppm), and P6 (500 ppm decis/positive control) were the treatments employed. 280 leaf roller caterpillars served as the test subjects. The study's findings after 48 hours of observation under the P5 treatment indicated that shallot skin extract had a fatality rate of 100%, killing 40 test animals. The study's finding is that shallot skin extract significantly affects how many leaf roller caterpillars die.